2020
DOI: 10.1177/0973408220930708
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Children’s Well-being with Art in Nature: Artist Pedagogue Perceptions

Abstract: There is increasing concern about children’s mental well-being and an urgent need for research into how to support positive mental health; including as part of the United Nations Sustainable Development Goals (SDGs). Alongside this is the heightened awareness about diminished access to green spaces and diminished exposure to the arts for children. Our research aims to show the potential for addressing these three issues in tandem through a qualitative case study exploring the work of one charity, Cambridge Cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…Andresen & Fegter, 2011 ; Coverdale & Long, 2015 ; Fane et al, 2020 ; Fattore et al, 2009 ). As detailed in the literature review, previous studies have demonstrated how human-nature connectedness has a restorative effect for children’s wellbeing (Milligan & Bingley, 2007 ; Rudkowski, 2014 ; Walshe et al, 2020b ; Walshe et al, 2020a ); within this study a small percentage of children at least appear to recognise this. For the remaining 39 children for whom nature is not foregrounded in their drawings but is present in some form or other, there is a concern that if the connections between nature and wellbeing remain only implicit, it may be less likely that they will get involved in conscious efforts to protect and sustain the environment (Milstein, 2011 ).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Andresen & Fegter, 2011 ; Coverdale & Long, 2015 ; Fane et al, 2020 ; Fattore et al, 2009 ). As detailed in the literature review, previous studies have demonstrated how human-nature connectedness has a restorative effect for children’s wellbeing (Milligan & Bingley, 2007 ; Rudkowski, 2014 ; Walshe et al, 2020b ; Walshe et al, 2020a ); within this study a small percentage of children at least appear to recognise this. For the remaining 39 children for whom nature is not foregrounded in their drawings but is present in some form or other, there is a concern that if the connections between nature and wellbeing remain only implicit, it may be less likely that they will get involved in conscious efforts to protect and sustain the environment (Milstein, 2011 ).…”
Section: Discussionsupporting
confidence: 50%
“…We have begun to explore the role of the arts and nature on children’s wellbeing through a number of recent studies and publications. In the most recent article investigating artist pedagogue perceptions of supporting children’s wellbeing through art in nature (Walshe et al, 2020b ), our review of the literature suggested that, although there are proven links separately between nature and wellbeing, and art and wellbeing, there are very few examples of the amalgamation of both. In these few cases, the benefits for children’s wellbeing were highlighted.…”
Section: Introductionmentioning
confidence: 96%
“…They also echo Yarwood and Tyrrell's (2012) calls for informing teaching and research, and Hammond (2021a) arguments about the importance of relationships between children's everyday lives and geographical education to encourage 'dialogic conversation' (Hammond, 2021b: 13) across pedagogy, curriculum and research. In sharp contrast to previous characterisations of the field of geography education research as unfunded, there has been an increase in funded research in the field across RCUK (Research Councils United Kingdom), GCRF (Global Challenges Research Fund), EU (European Union) and beyond, for example, fostering collaborations between geography education researchers and artists (Walshe et al, 2020) and geography teacher educators internationally (Uhlenwinkel et al, 2016). Noxolo's CARICUK (Creative Approaches to Race and In/security in the Caribbean and the UK) project 5 is an important example of work being fostered through relationships across geography education, making significant contributions to discussions in the discipline while also nurturing a dialogic engagement with public geographies and the school subject.…”
Section: Interactions and Relationshipsmentioning
confidence: 93%
“…There is evidence that arts education can improve both wellbeing and social inclusion (e.g., [68,69]), as well as developing children's capabilities [70]. Arts based approaches have been found to support the development of the qualities on Nussbaum's [39] list of capabilities: for example, arts performance through kinaesthetic forms such as dance and theatre have a demonstrated impact on bodily health and bodily integrity [71]; while engagement with visual arts has been shown to improve imagination and thought [72] and emotional skills (e.g., [73,74]).…”
Section: The Arts As a Mechanism For Developing Capabilities And Well...mentioning
confidence: 99%
“…Previous studies have demonstrated how human-nature connectedness has a restorative effect for children's wellbeing (e.g., [68,95,96]). Ulrich's psycho-evolutionary theory [97], describes humans' innate affiliation with natural environments, drawing upon the assumption that natural environments induce positive emotions and feelings [98].…”
Section: (Teacher Interview)mentioning
confidence: 99%